ANALISIS PENGARUH PENGELUARAN PEMERINTAH DI SEKTOR PENDIDIKAN, SEKTOR KESEHATAN, SEKTOR INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA (PERIODE TAHUN 2010-2017) - Jofani Mega Puspitasari; Sudati Nur Sarfiah; Rusmijati . (Universitas Tidar, 2019)
This study aims to determine the effect of government spending in the education sector, health sector, infrastructure sector on Indonesia's economic growth. This research is classified as associative quantitative research. The data analysis method used in this study is a multiple linear regression analysis tool with the help of Statistical Package for Solution Solution (SPSS). The data in this study used Indonesian secondary data from 2010 to 2017. The statistical tests in this study used the classic assumption test including (normality test, heteroscedasticity test, multicollinearity test autocorrelation test), t test, f test, and test R2. The results showed that: 1. Variables of government expenditure in the education sector partially showed a positive and significant nfluence on economic growth in Indonesia. 2. Variable government expenditure in the health sector partially shows a positive and significant influence on economic growth in Indonesia. 3. Variable government expenditure in the infrastructure sector partially shows a positive and significant influence on economic growth in Indonesia. 4. Variable government expenditure in the education sector, health sector, infrastructure sector together have a significant influence on economic growth in Indonesia. Keywords: Government Expenditures, Education, Health, Infrastructure, Economic Growth.